2018
DOI: 10.1002/fut.21941
|View full text |Cite
|
Sign up to set email alerts
|

Correlation risk and international portfolio choice

Abstract: Variance‐covariance risk of the exchange rate is highly relevant for international investors. This paper addresses optimal asset allocation with stochastic variances and covariances in a Wishart Affine Stochastic Correlation (WASC) model in incomplete and complete markets. We show that the (hedging) demand for exchange rate variance‐covariance risk can differ significantly between international investors. Local correlations with the exchange rate can affect the utilities of international investors differently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Previous findings show that depending on the currency exchange rate correlations, foreign investors can benefit more than domestic investors from international trading. Branger, Muck, and Weisheit (2019) explain that correlations with the exchange rate can affect the utilities of foreign investors differently, while the impact of relationships between stocks can be symmetric. In that regard, Dwumfour and Addy (2019) found that only depreciation of the Ghana local currency against the U.S. dollar, but not against Britain Pounds or Euro, reduces the portfolio stock returns.…”
Section: International Portfolio Theory and Foreign Exchange Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings show that depending on the currency exchange rate correlations, foreign investors can benefit more than domestic investors from international trading. Branger, Muck, and Weisheit (2019) explain that correlations with the exchange rate can affect the utilities of foreign investors differently, while the impact of relationships between stocks can be symmetric. In that regard, Dwumfour and Addy (2019) found that only depreciation of the Ghana local currency against the U.S. dollar, but not against Britain Pounds or Euro, reduces the portfolio stock returns.…”
Section: International Portfolio Theory and Foreign Exchange Derivativesmentioning
confidence: 99%
“…Some authors have performed empirical studies to analyze the effect of hedging strategies with derivatives on firm value (Guay & Kothari, 2003;Bartram et al, 2011), or on portfolio allocation (Demange & Laroque, 1999;Branger et al, 2019). Findings have proved the negative effect of the lack of hedging practices on exchange rate exposure (Bhargava & Malhotra, 2007), suggesting that exchange rate exposure is negatively related to derivatives usage (Anderson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Combining multiple risky assets with poor inter-correlation can significantly reduce unsystematic risk [2]. It not only keeps the effective frontier of portfolio away from risk, but also enables investors with specific risk preferences to obtain more risk returns in the financial market [3]. Therefore, with the increasing maturity of the financial market, the majority of investors in order to obtain a better marginal return on capital and less risk, portfolio management has become an urgent issue for them to consider [4].…”
Section: Introductionmentioning
confidence: 99%
“…Arbitrage Pricing Theory), financial stability or risk management, time-varying volatilities and correlations matter (Embrechts et al , 2002; Andersen et al , 2007). For example, studies by Krishnan et al (2009), Driessen et al (2009) and Buss et al (2017) study the pricing of variance and correlation risk, and Branger et al (2018) study the effect of stochastic covariances on the behaviour of international investors.…”
Section: Introductionmentioning
confidence: 99%